Role of Ca2+ in the IVM of spermatozoa from the sterlet Acipenser ruthenus - Bondarenko, Olga; Dzyuba, Borys; Rodina, Marek; Cosson, Jacky (Reproduction, fertility, and development, 2017)
The role of Ca2+ in sturgeon sperm maturation and motility was investigated. Sperm from mature male sterlets (Acipenser ruthenus) were collected from the Wolffian duct and testis 24h after hormone induction. Testicular spermatozoa (TS) were incubated in Wolffian duct seminal fluid (WDSF) for 5min at 20°C and were designated 'TS after IVM' (TSM). Sperm motility was activated in media with different ion compositions, with motility parameters analysed from standard video microscopy records. To investigate the role of calcium transport in the IVM process, IVM was performed (5min at 20°C) in the presence of 2mM EGTA, 100µM Verapamil or 100µM Tetracaine. No motility was observed in the case of TS (10mM Tris, 25mM NaCl, 50mM Sucr with or without the addition of 2mM EGTA). Both incubation of TS in WDSF and supplementation of the activation medium with Ca2+ led to sperm motility. The minimal Ca2+ concentration required for motility activation of Wolffian duct spermatozoa, TS and TSM was determined (1-2nM for Wolffian duct spermatozoa and TSM; approximately 0.6mM for TS). Motility was obtained after the addition of verapamil to the incubation medium during IVM, whereas the addition of EGTA completely suppressed motility, implying Ca2+ involvement in sturgeon sperm maturation. Further studies into the roles of Ca2+ transport in sturgeon sperm maturation and motility are required.
Keywords: Calcium; Culture Media; Male; Sperm Motility; kultivační média; vápník; techniky in vitro; Spermatozoa; mužské pohlaví; blokátory kalciových kanálů; Testis; iontový transport; ryby; Fishes; sperma; Verapamil; Semen; Animals; Calcium Channel Blockers; Wolffian Ducts; Wolffovy vývody; Ion Transport; zvířata; testis; motilita spermií; spermie; zrání spermie; Sperm Maturation; In Vitro Techniques; verapamil